‘It means you can’t see all the children’: analysing school staff’s experiences of tackling pupil loneliness through an ecological systems lens - Joakim Strindberg (International Journal of Adolescence and Youth)
Over the past three or four years, loneliness has been highlighted as a significant problem in Swedish schools. While staff-pupil relationships have been identified as important in dealing with such experiences, relatively little attention has been paid to the capacity of staff to do so. In this study I analyse the experiences of staff in dealing with student loneliness in schools. The discussions are based on 11 interviews with 16 school staff and their experiences were analysed using Bronfenbrenner’s (1979) theory of ecological systems. The findings highlight two main concerns of staff working with loneliness: (1) the potential of relationships, including the importance of caring relationships at the micro- and mesosystem levels of the school, and (2) the ways in which working with caring relationships can be overridden by exo-, macro- and chronosystem issues, such as staff shortages, staff workload and demands on pupils’ academic performance. Key implications are discussed.